2017
DOI: 10.1212/wnl.0000000000003883
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, psychological morbidity, job stress, and job satisfaction in Chinese neurologists

Abstract: Burnout and psychological morbidity are common in Chinese neurologists. Burnout is the single greatest predictor of neurologists' psychological morbidity, high job stress, and low job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 25 publications
8
65
1
1
Order By: Relevance
“…Through univariate analysis, we found that, compared to the group working in the dermatology group, those working in the surgeon sector suffered from occupational stress with the rate of 8.8 times higher (11.9% compared to 1.5%). This result similar to research in China in 2017 and India in 2018 (20,28). This is consistent with the reality at the hospital.…”
Section: The Relationship Between Stress Status According To Some Chasupporting
confidence: 92%
“…Through univariate analysis, we found that, compared to the group working in the dermatology group, those working in the surgeon sector suffered from occupational stress with the rate of 8.8 times higher (11.9% compared to 1.5%). This result similar to research in China in 2017 and India in 2018 (20,28). This is consistent with the reality at the hospital.…”
Section: The Relationship Between Stress Status According To Some Chasupporting
confidence: 92%
“…The results of this study demonstrated a high prevalence of burnout syndrome in neurologists in Paraná, comparable with recent publications. Physicians in specialties at the front line of health care access, such as emergency medicine and general internal medicine, are at a greater risk of burnout syndrome, according to previous studies 3,18 . With the new categorization of stroke neurologists, who are responsible for the emergency care of stroke, particularly caring for hyperacute and acute strokes, which started mainly in the 2000s 19 , this could theoretically have led to a higher prevalence of burnout syndrome in this specific new setting.…”
Section: Discussionmentioning
confidence: 96%
“…There is no doubt that it is essential to monitor these issues as they unfold and explore the relationship between doctors' career calling and burnout in depth. Doctors exhibit reduced enthusiasm for their work due to emotional exhaustion, a decline in professional meaningfulness, job satisfaction, and organizational identification [25]. When doctors are treated unfairly, their enthusiasm diminishes with in-role weakening and extrarole decreasing, [26] resulting a loss of psychological attachment to their organization [26].…”
Section: What Is the Relationship Between Career Calling Psychologicmentioning
confidence: 99%